Teori Taksonomi Bloom serta Cabaran Guru Pendidikan Islam dalam Mengaplikasi Kemahiran Berfikir Aras Tinggi (KBAT) Pengajaran Akidah Menurut Perspektif Jurulatih Utama Negeri (JU) Sekolah Rendah dan Menengah: Bloom’s Taxonomy and the Challenges Faced by Islamic Education Teachers in Applying Higher Order Thinking Skills (HOTS) in Teaching Aqidah from the Perspective of State Trainers (JU) in Primary and Secondary Schools - Yusoff, Pauzi; Hamat, Mohd Fauzi; Mohamed Adnan, Mohamad Azrien (Jurnal Usuluddin, 2024)
The emphasis on critical thinking skills remains the primary focus in 21st-century thinking skills. However, the implementation of Higher Order Thinking Skills (HOTS) is deemed not fully achievable yet by Islamic Education teachers (GPI) in the teaching and learning sessions of the aqidah field. This study focuses on the challenges faced by Islamic Education teachers instructing the aqidah field based on the Document of Content and Assessment Standards (DSKP), as per the perspectives of State trainers (JU). The research design employs a semi-structured interview method, and the gathered data is thematically analyzed using ATLAS.ti V8 software. Ten participants were selected to represent five zones in Malaysia. These State trainers are expert teachers with extensive experience in Islamic religious education, recognized under the Ministry of Education Malaysia. The selected zones include one participant from a primary school and one from a secondary school in the Northern, Southern, Eastern, Central, and East Malaysia (Sabah) zones. Findings indicate that integrating Bloom’s taxonomy framework into HOTS aqidah teaching faces challenges for GPI due to three major obstacles: individual teacher aspects, internal and external administrative issues, and student aspects with various interpretations.